Structural composition of organic matter in particle-size fractions of soils along a climo-biosequence in the main range of Peninsular Malaysia - Haghighi, Amir Hossein Jafarzadeh; Jusop, Shamshuddin; Jol, Hamdan; Zainuddin, Norhazlin (De Gruyter Open, 2016)
Information on structural composition of organic matter (OM) in particle-size fractions of soils along a climo-biosequence is sparse. The objective of this study was to examine structural composition and morphological characteristics of OM in particle-size fractions of soils along a climo-biosequence in order to better understand the factors and processes affecting structural composition of soil organic matter. To explore changes in structural composition of OM in soils with different pedogenesis, the A-horizon was considered for further analyses including particle-size fractionation, solid-state 13C nuclear magnetic resonance (NMR) spectroscopy and scanning electron microscopy (SEM). Due to the increase in the thickness of organic layer with increasing elevation, the A-horizon was situated at greater depth in soils of higher elevation. The relationship between relative abundances of carbon (C) structures and particle-size fractions was examined using principal component analysis (PCA). It was found that alkyl C (20.1-73.4%) and O-alkyl C (16.8-67.7%) dominated particle-size fractions. The proportion of alkyl C increased with increasing elevation, while O-alkyl C showed an opposite trend. Results of PCA confirmed this finding and showed the relative enrichment of alkyl C in soils of higher elevation. Increase in the proportion of alkyl C in 250-2000 μm fraction is linked to selective preservation of aliphatic compounds derived from root litter. SEM results showed an increase in root contribution to the 250-2000 μm fraction with increasing elevation. For the <53 μm fraction, pedogenic process of podzolization is responsible for the relative enrichment of alkyl C. This study demonstrates that changes in structural composition of OM in particle-size fractions of soils along the studied climo-biosequence are attributed to site-specific differences in pedogenesis as a function of climate and vegetation.